Digital Craft - Monica Ponce de Leon (Oz, 2011)
As we ponder the present and future of the field of architecture, it might be helpful to look at the history of design. Different versions of many of the debates currently played out in the design media, in academic conferences and in our classrooms were rehearsed at the advent of the industrial revolution and revisiting them may shed light on our present predicaments.